'From Kyangwali to Sydney' Life History Narrative and Postcolonial Theory in Refugee Educational Studies. (1st May 2019) - Mupenzi, Alfred; Naidoo, Loshini; Gannon, Susanne
This paper presents a narrative written by Alfred drawing on his life journey as a refugee in order to consider the nexus between individual life history and national and regional histories, postcolonial theories and educational trajectories for refugee background students. Educational success for students of refugee backgrounds is of continuing concern for educational institutions, policymakers and teachers at all levels. Although researchers stress the need to push back against deficit perceptions of refugee students, their research tends to focus on lack whether this is located in individual learners, communities or families, pedagogical approaches, or provision. Most research also usually focuses experience within their current educational context, although researchers will often note in passing that previous life experiences have continuing educational repercussions. Although considerable research has focused on pathways into higher education, analysis of the intricacies of individual life histories and how these are intertwined with larger historical forces have been overlooked. This paper advocates bringing previous educational and life experiences before settlement to the centre of refugee studies in order to recognise educational capacities developed by students of refugee backgrounds. Furthermore, it draws on a postcolonial analysis to examine how an individual narrative may be embedded in and shaped by national, regional and supranational discourses and histories.